2015
DOI: 10.1016/j.canlet.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of survivin-targeted therapy on chemosensitivity in the treatment of acute myeloid leukemia

Abstract: Overexpression of survivin is observed in various hematological malignancies, including acute myeloid leukemia (AML). Studies show that elevated expression of survivin correlates with a worse clinic outcome in AML patients. It remains unclear whether inhibition of survivin may alter the efficacy of chemotherapy against AML. Here, we evaluate the effects of specific knockdown of survivin on AML cells’ sensitivity to chemotherapy, and investigate the therapeutic potential of the transcription inhibitor of surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
9
23
0
2
Order By: Relevance
“…These finding are consistent with previously published survival analysis using TCGA database demonstrating prolonged survival in AML patients with lower survivin expression . Furthermore, our analysis of this database of 168 adult AML patients confirmed that patients with low MUC1 expression showed significantly prolonged overall survival ( P = .02, data not shown).…”
Section: Resultssupporting
confidence: 93%
“…These finding are consistent with previously published survival analysis using TCGA database demonstrating prolonged survival in AML patients with lower survivin expression . Furthermore, our analysis of this database of 168 adult AML patients confirmed that patients with low MUC1 expression showed significantly prolonged overall survival ( P = .02, data not shown).…”
Section: Resultssupporting
confidence: 93%
“…Lentiviral production was performed as described [17, 51]. In brief, the lentiviral expression vector pLKO.1-ConshRNA or pLKO.1-SurshRNA; pLEX-Luc or pLEX- hSurvivin ; miRZip control, miRZip-203, or miRZip-542-3p and the packaging plasmids psPAX2 and pMD2.G were co-transfected into HEK293T cells.…”
Section: Methodsmentioning
confidence: 99%
“…Tingkat ketahanan sel yang menurun dapat diasumsikan sebagai peningkatan apoptosis yang dapat berkorelasi dengan penurunan ekspresi survivin. 15 Rendahnya nilai hemoglobin baik disebabkan karena adanya supresi sumsum tulang akibat proliferasi sel kanker, maupun karena adanya perdarahan akibat rendahnya trombosit sangat berpengaruh terhadap prognosis pasien. Penundaan pemberian kemoterapi akan berdampak pada overekspresi dari sel ganas, dan proliferasi multi organ.…”
Section: Pembahasanunclassified
“…Pasien dengan hemoglobin dan trombosit rendah memerlukan koreksi sebelum diberikan obat kemoterapi. 16 Pada 15 Prediksi terjadinya kemoresistensi menjadi perhatian yang penting dan pemantauan pada pasien LLA. Terdapat hubungan antara prognosis yang buruk dan adanya sel blast pada 10 hari setelah kemoterapi fase induksi yang telah banyak dipahami para klinisi sebagai dasar untuk memulai reinduksi.…”
Section: Pembahasanunclassified